Kidney Size, Renal Function, Ang (Angiotensin) Peptides, and Blood Pressure in Young Adults Born Preterm: The HAPI Study. Issue 4 (October 2018) - Paquette, Katryn; Fernandes, Rafael Oliveira; Xie, Li Feng; Cloutier, Anik; Fallaha, Catherine; Girard-Bock, Camille; Mian, Muhammad Oneeb Rehman; Lukaszewski, Marie-Amélie; Mâsse, Benoit; El-Jalbout, Ramy; Lapeyraque, Anne-Laure; Santos, Robson A.; et al.
Abstract : Preterm birth incurs a higher risk for adult cardiovascular diseases, including hypertension. Because preterm birth may impact nephrogenesis, study objectives were to assess renal size and function of adults born preterm versus full term and to examine their relationship with blood pressure (BP; 24-hour ambulatory BP monitoring) and circulating renin-Ang (angiotensin) system peptides. The study included 92 young adults born (1987–1997) preterm (⩽29 weeks of gestation) and term (n=92) matched for age, sex, and race. Young adults born preterm had smaller kidneys (80±17 versus 90±18 cm 3 /m 2 ; P <0.001), higher urine albumin-to-creatinine ratio (0.70; interquartile range, 0.47–1.14 versus 0.58, interquartile range 0.42 to 0.78 mg/mmol, P =0.007), higher 24-hour systolic (121±9 versus 116±8 mm Hg; P =0.001) and diastolic (69±5 versus 66±6 mm Hg; P =0.004) BP, but similar estimated glomerular filtration rate. BP was inversely correlated with kidney size in preterm participants. Plasma Ang I was higher in preterm versus term participants (36.3; interquartile range, 13.2–62.3 versus 19.4; interquartile range, 9.9–28.1 pg/mL; P <0.001). There was no group difference in renin, Ang II, Ang (1–7), and alamandine. In the preterm, but not in the term group, higher BP was significantly associated with higher renin and alamandine and lower birth weight and gestational age with smaller adult kidney size. Young adults born preterm have smaller kidneys, higher urine albumin-to-creatinine ratio, higher BP, and higher circulating Ang I levels compared with term controls. Preterm young adults with smaller kidneys have higher BP. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03261609. Abstract : Supplemental Digital Content is available in the text.